2008
DOI: 10.1080/09540100802520755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indirect competitive and double antibody sandwich ELISA tests to determine β-lactoglobulin and ovomucoid in model processed foods

Abstract: Enzyme-linked immunosorbent assay (ELISA) kits (indirect competitive and sandwich formats) to determine either b-lactoglobulin or ovomucoid were evaluated in model foods. A cut-off value was established for each kit to consider food samples as positive for milk or egg addition. Sausage and bread were positive at lower percentages of added milk using the sandwich format (0.005 and 0.05%) than the indirect competitive format (0.05 and 0.25%) and pâté was positive at 0.25% milk addition for both formats. Sausage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The immunosensor was applied to spiked egg-white samples as well as to spiked wheat flour and bread samples, obtaining results in accordance with literature data (eggwhite samples) [85] and lower than those coming from the ELISA method (wheat flour and bread) [86].…”
Section: Immunosensorssupporting
confidence: 78%
“…The immunosensor was applied to spiked egg-white samples as well as to spiked wheat flour and bread samples, obtaining results in accordance with literature data (eggwhite samples) [85] and lower than those coming from the ELISA method (wheat flour and bread) [86].…”
Section: Immunosensorssupporting
confidence: 78%
“…It was applied to the analysis of wheat flour and baked bread supplemented with lyophilized egg at trace levels with ability to detect 0.17 and 0.13 ppm of egg in raw (wheat flour) and cooked (baked bread) samples, respectively. These values were four orders of magnitude lower than those provided by commercial ELISA kits and those considered relevant for the determination of allergens (10 mg Kg −1 [51,52]). Importantly, it was possible to detect only 5 ppm of egg by a simple incubation of the CAb-MBs in turbid samples with a high content of suspended solid matter to perform the direct and efficient ovomucoid capture (Figure 2b).…”
Section: Electrochemical Immunosensing Methodsmentioning
confidence: 64%
“…Therefore, determination of the recovery in samples incurred before the application of any processing is more accurate and should be applied in a proper validation process of any analytical method. Several studies in which evaluation of the robustness by incurring samples before processing was done are published. , We have shown that when determining the robustness in cookies incurred before processing was applied, only about 10% recovery were obtained . Similarly, the recovery of the DNA seems to also be affected by processing, mainly because of its degradation and/or hindered extractability …”
Section: Quantification Of Food Allergensmentioning
confidence: 99%